IMPLEMENTASI KEBIJAKAN PELAYANAN PENERBITAN SIM DI KOTA PEKANBARU TAHUN 2015 – 2016 (STUDI KONSISTENSI PERATURAN KAPOLRI NOMOR 9 TAHUN 2012 TENTANG SIM) - Andi Larosa Lorera Villani; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The implementation of the policy in principle is a way so that a policy can achieve its purpose. Policy implementation is the most important stage in the process of policy. Assistant Regulation number 9 Year 2012 about SIM aims in order to make the code of conduct services in the issuance of a DRIVER'S LICENSE that is transparent, effective, efficient, and accountable with the principle of legality, professional, proportionate, transparency, accountability and participatory.The purpose of this research is to know the publishing service of the SIM implementation and to know the factors that hampered in the implementation of the policy of the Ministry of the publishing LICENCE. This type of research is a qualitative descriptive method and location of the research carried out at the unit Office of traffic Polresta Pekanbaru.The analysis of the data found in the study used research formula to answer by using the theory of analysis of the factors affecting the implementation of the policies of Charles Edward III that those factors is communication, sources, trend-trend or behavior and bureaucratic structure.The results of the analysis of the resulting data indicated that implementation of the policy of the Ministry of the Publishing LICENCE has not been going well for in influence by factors of communication, resources, bureaucratic structure and disposition of implementation. In addition about the factors that affect the implementation of the policy of the Ministry of the issuance of driver's license, other research results regarding the implementation of a policy that until now has not been fullest due to the presence of a factor of availability of resources less, the compliance of the community, the lack of control and supervision, and the integrity of the implementing policy.Keywords : Implementation, Policy, Service